The expression of inflammatory markers and their potential influence on efflux transporters in drug‐resistant mesial temporal lobe epilepsy tissue. (21st July 2018) - Weidner, Lora D.; Kannan, Pavitra; Mitsios, Nicholas; Kang, Sun J.; Hall, Matthew D.; Theodore, William H.; Innis, Robert B.; Mulder, Jan
Summary: Objective: The role of neuroinflammation in mesial temporal lobe epilepsy (MTLE), and how it relates to drug resistance, remains unclear. Expression levels of the inflammatory enzymes cyclooxygenase (COX)‐1 and COX‐2 have been found to be increased in animal models of epilepsy. Knowing the cellular expression of COX‐1 and COX‐2 is the key to understanding their functional role; however, only 3 studies have investigated COX‐2 expression in epilepsy in humans, and there are no reports on COX‐1. In addition, previous studies have shown that certain inflammatory proteins up‐regulate ATP binding cassette (ABC) transporter expression (thought to be responsible for drug resistance), but this relationship remains unclear in human tissue. This study sought to measure the expression of COX‐1, COX‐2, and translocator protein 18 kDa (TSPO, an inflammation biomarker acting as a positive control), as well as ABC transporters P‐glycoprotein (P‐gp) and breast cancer resistance protein (BCRP), in brain tissue samples from people with drug‐resistant MTLE. Methods: Formalin‐fixed paraffin‐embedded surgical brain tissue was obtained from 33 patients with drug‐resistant MTLE. Multiplex immunofluorescence was used to quantify the expression and distribution of COX‐1, COX‐2, TSPO, P‐gp, and BCRP. Results: COX‐1 was expressed in microglia, and COX‐2 and TSPO were expressed in microglia and neurons. BCRP density correlated significantly with TSPO density, suggesting a potential relationship between inflammatory markers and efflux transporters. Significance: To the best of our knowledge, this study is the first to measure the cellular expression of COX‐1, COX‐2, and TSPO in microglia, astrocytes, and neurons in surgical brain tissue samples from patients with drug‐resistant MTLE. Further research is needed to determine the effects of the COX inflammatory pathway in epilepsy, and how it relates to the expression of the ABC transporters P‐gp and BCRP.